SOSIALISASI TANPA ASAP ROKOK DI RUMAH SAKIT UMUM SEMBIRING DELI TUA - Herlina J. El-Matury; Selamat Ginting; Saiful Batubara (INSTITUT KESEHATAN DELI HUSADA, 2021)
Smoking is a culture in society that has been going on for a long time and is still a health problem in Indonesia. Hospitals as health care centers should demonstrate a healthy culture and behavior in all aspects, including being free from cigarette smoke. The problem that is often encountered by the Sembiring Deli Tua General Hospital is that there are still health workers and hospital visitors who smoke in the hospital environment, even though various warning signs are prohibited from smoking in almost all strategic points of the hospital area. In order to strengthen the smoke-free hospital movement, socialization was carried out to hospital employees and hospital visitors in the form of distributing leaflets and brief information about healthy behavior without smoking which was carried out during February 2021, with the hope that this socialization would be able to realize the Sembiring Deli General Hospital. Old as a smoke-free area.